K-score categorisation of JSE listed sectors under the financial distress continuum theory: a quantitative approach - Navitha Singh Sewpersadh (Cogent Economics & Finance, 2020)
Purpose: The liquidation culture in South Africa has proven to be disastrous for its macroeconomic and social goals. Premised on the financial distress continuum theory, which not only determines investment, but also provides early warning signals for firms to pursue remedies, this article investigated the financial health and stability of listed firms. To detect and/or remedy the negative consequences of corporate failures in a timely manner, this study employed the De la Rey K-score model as a risk-based model. Design: The investigation period was over six years with a final sample of 673 company-year observations. This study used the statistical methods of one-way ANOVA and OLS. Findings: The results indicated that the average K-scores from 2011 to 2016 have severely declined, illustrating the magnitude of financial distress among industries. The mean K-score is in the healthy range for the consumer services and consumer goods sectors for each year of the investigation period. This study found that the telecommunications and health care sectors were classified as "grey" zone, which exhibited considerable inter-year variation in financial health. Whilst the industrial and technology sectors were financially distressed. This study also found a significantly positive relationship between the K-score and performance variables. Recommendations: This study recommends that the grey zone sectors should consider turnaround strategies to prevent companies from regressing into the financially distressed category. Furthermore, the distressed sectors should consider embarking on the two pre-insolvency proceedings in the Companies Act (2008). Originality: This study uniquely applied the K-score model as an early warning signal for financial distress and linked the K-score model to the financial distress continuum theory. The results of this study have important implications for policymakers, practitioners, and regulatory authorities, especially those in emerging economies.
Keywords: 330; early warning signals; financial distress; K-score; JSE